Field reports of Iowa birds contributed by Thomas H. Kent, November 26, 1988 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1988)
List of birds and locations contributed by Thomas H. Kent with observers Francis L. Moore, James L. Fuller and Carl J. Bendorf. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1988. Epson - sheet feed